2022
DOI: 10.55145/ajbms.2022.1.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Study The Causative agent of abortion in Babylon city by using TORCH test.

Abstract: TORCH syndrome is only one health issue. According to health experts, however, TORCH syndrome is a set of various infectious diseases. They can cause serious problems and can damage a fetus' health. Aim of study: To detection the causative agent of abortion in Babylon city –Iraq by using TORCH test . Material and patient : Hundred ninety five women severed from abortion were enrolled in this study .The duration of study continuous from July 2018-to June 2019. ELISA test was used for determination the tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…People with certain genetic variants can develop immune responses as a result of exposure to certain components of the diet; This leads to the development of autoimmune disorders such as celiac disease and Hashimoto's thyroiditis (20,21).…”
Section: Dietary Factorsmentioning
confidence: 99%
“…People with certain genetic variants can develop immune responses as a result of exposure to certain components of the diet; This leads to the development of autoimmune disorders such as celiac disease and Hashimoto's thyroiditis (20,21).…”
Section: Dietary Factorsmentioning
confidence: 99%
“…These enzymes often determine the hepatic condition and their management. These hepatocellular enzymes, which seep into the bloodstream due to a liver damage, comprise the liver cells, thus, offering very important pieces of information on the state and the kind of injury (6)(7)(8)(9) .…”
Section: Role Of Hepatic Enzymes In Liver Diseasementioning
confidence: 99%
“…Some concerns about the possible thyroid-disruptive effects of some phytocompounds, such as soy isoflavones (e.g., genistein and daidzein), have been raised (8) , Many studies have been showed considering the prevalence of thyroid dysfunction in b-thalassaemic patients. Surprisingly, the incidence of thyroid dysfunction reported varies widely from low to 60% and the prevalence of overt hypothyroidism ranges from 0% up to almost 20% of patients from different series (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%